Globalizing Global Skill Partnerships and Africapitalism as a sustainable aid response to the irregular migration crisis between Cameroon and Europe. - Zukane Retruyap, Mbuih (Advances in Social Sciences Research Journal, 2018)
Discourses on skilled workers’ migration from Africa to Europe was enthralled around brain drain. Today, the trend is more focused on brain waste as a good number of irregular skilled migrants are obliged to do mean jobs abroad. My main argument focuses on the demand and supply of skilled labor. Building on the fact that in 2050, 34% of Europe’s population will be made up of 60+ (demand), while Africa will have 800 million youths (supply). Following this trend, a global partnership scheme for migrants is vital in managing skilled migrants through training and complementarity, thereby regulating the issues around irregular migration. I proposed the usage of Africapitalism as a new modus operandi that the EU will use as an alternative to solve the root causes of irregular migration.